Assessing the Cost of Prophylactic Antibiotic Use After Cleft Lip and Lip Adhesion Procedures. Issue 4 (July 2016) - Daniels, Kimberly M.; Lappi, Michael D.; Sporn, Susan Flath; Caillouette, Catherine Noonan; Heald, Ronald; Meara, John G.
Abstract : EXECUTIVE SUMMARY : The purpose of this study was to understand the true cost of administering prophylactic antibiotics postoperatively to patients undergoing cleft lip and lip adhesion procedures for which the rate of infection is historically low. Using time‐driven activity‐based costing (TDABC) methodologies, the plastic surgery department of one hospital created a process map with related time intervals and personnel cost rates for administering the antibiotic. The cost for each provider, based on standard salary information, was multiplied by the time required to complete his or her stage of the process, and this outcome was added to the supply costs. Overall cost was determined by summing the cost of all the steps. The cost of administering four doses of ampicillin/sulbactam to a patient during an inpatient stay ranged from 61.91 to 81.83. The total cost included all steps, from the initial antibiotic prescription through the final administration by a nurse. We attributed variations in cost to the staff member's level of familiarity with the antibiotic and dosing protocols for that patient. Over the course of a year, the cost of administering prophylactic antibiotics for this patient population was between 3, 281.23 and 4, 336.99. The results of this study effectively demonstrate the use of TDABC to determine the cost of administering prophylactic postoperative antibiotics. If we assume that antibiotics are of limited value for all clean‐contaminated plastic surgery procedures, the plastic surgery department can expect to save 18, 000 to 22, 000 each year by forgoing their use. Furthermore, when clinically supported, reducing the use of prophylactic antibiotics not only diminishes the cost of care but also reduces the complexity of postoperative care.